1986
DOI: 10.1093/ajcn/44.3.315
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the doubly labeled water (2H218O) method with indirect calorimetry and a nutrient-balance study for simultaneous determination of energy expenditure, water intake, and metabolizable energy intake in preterm infants

Abstract: The doubly labeled water method was compared with indirect calorimetry and a nutrient-balance study for simultaneous determination of rates of CO2 production, energy expenditure, and water intake over 5 days in four preterm infants. Additionally, metabolizable energy (ME) intake estimated using the isotope procedure (as energy expenditure plus an estimate for energy deposition based on weight gain), was compared to ME intake measured in the balance study. Compared to values obtained by traditional methods, cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(71 citation statements)
references
References 18 publications
6
64
0
1
Order By: Relevance
“…The DLW technique is non-invasive, completely safe and involves minimal subject burden. The technique enables a precise estimation of metabolizable energy intake among free-living individuals, including infants and young children (Roberts et al, 1986;Jones et al, 1987). The mean TEE in the current study was 309 ± 46 kJ/kg/day for the 9-month-old infants.…”
Section: Discussionmentioning
confidence: 58%
“…The DLW technique is non-invasive, completely safe and involves minimal subject burden. The technique enables a precise estimation of metabolizable energy intake among free-living individuals, including infants and young children (Roberts et al, 1986;Jones et al, 1987). The mean TEE in the current study was 309 ± 46 kJ/kg/day for the 9-month-old infants.…”
Section: Discussionmentioning
confidence: 58%
“…It is noteworthy that the differ OBES ITY RESEARCH Vol. ence between the rates of 2H and 18o disappearance was extremely small in this subject, with a kc/kd ratio comparable to that found in premature infants (9). Under these circumstances, the doubly labeled water method becomes very sensitive to analytical error (8) and error can be expected to be increased by more than 50% relative to those observed wben k 0 /kd is 1.3 .…”
Section: Human Subjectssupporting
confidence: 50%
“…Since its frrst application to human subjects over a decade ago (14) several validation studies in adult and infant subjects have compared the doubly labeled water method with nearly-continuous indirect calorimetry (1,6,7,9,13,(15)(16)(17) . These studies have consistently shown a close agreement between values for carbon dioxide production determined by the two techniques.…”
Section: Introductionmentioning
confidence: 99%
“…4 The DLW method has been validated against both gaseous exchange (GE) (considered to be the gold standard for the estimation of energy expenditure (EE)), [5][6][7][8][9] and energy balance studies. 10,11 Some variation has been reported between the results of validation studies, which has been attributed to the different physiological states of the individuals and errors associated with different analytical methods undertaken by each laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…No study has investigated the validity of DLW in an obese group since that of Ravussin et al, 15 and other studies yielding individual subject data have not supported a relation between adiposity and error in DLW-estimated TEE. [6][7][8][9][10] There is now a pressing need to re-examine Ravussin's observations and, if they are confirmed, to explore further the mechanisms by which they may occur.…”
Section: Introductionmentioning
confidence: 99%